Pulsating flow of an incompressible micropolar fluid between permeable beds - Bitla, Punnamchandar; Iyengar, Telikicherla Kandala Venkatacharyulu Kandala Venkatacharyulu (Nonlinear Analysis: Modelling and Control, 2013)
The paper deals with the pulsating flow of an incompressible micropolar fluid through a channel bounded by permeable beds. The fluid is injected into the channel from the lower permeable bed with a certain velocity and is sucked into the upper permeable bed with the same velocity. The flow between the permeable beds is assumed to be governed by micropolar fluid flow equations and that in the permeable regions by Darcy law. The Beavers–Joseph (BJ) slip boundary conditions are used at the interfaces of the permeable beds. The governing equations are solved analytically and the expressions for velocity, microrotation, mass flux and shear stress are obtained. The effects of diverse parameters on the velocity and microrotation are studied numerically and the results are presented through graphs.
Keywords: pulsating flow; micropolar fluid; microrotation; Darcy law; BJ condition; permeable beds; shear stress